Relationships between ground reaction impulse and sprint acceleration performance in team sport athletes - Kawamori, N.; Nosaka, K.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2013)
Large horizontal acceleration in short sprints is a critical performance parameter for many team sport athletes. It is often stated that producing large horizontal impulse at each ground contact is essential for high short sprint performance, but the optimal pattern of horizontal and vertical impulses is not well understood, especially when the sprints are initiated from a standing start. This study was an investigation of the relationships between ground reaction impulses and sprint acceleration performance from a standing start in team sport athletes. Thirty physically active young men with team sport background performed 10-m sprint from a standing start, whereas sprint time and ground reaction forces were recorded during the first ground contact and at 8 m from the start. Associations between sprint time and ground reaction impulses (normalized to body mass) were determined by a Pearson's correlation coefficient (r) analysis. The 10-m sprint time was significantly (p < 0.01) correlated with net horizontal impulse (r = -0.52) and propulsive impulse (r = -0.66) measured at 8 m from the start. No significant correlations were found between sprint time and impulses recorded during the first ground contact after the start. These results suggest that applying ground reaction impulse in a more horizontal direction is important for sprint acceleration from a standing start. This is consistent with the hypothesis of training to increase net horizontal impulse production using sled towing or using elastic resistance devices, which needs to be validated by future longitudinal training studies.